2021
DOI: 10.1161/circep.120.009646
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Structural Inequities and Race With Out-of-Hospital Sudden Death During the COVID-19 Pandemic

Abstract: Background - Social influencers of health (SIOH) namely race, ethnicity and structural inequities are known to affect the incidence of out of hospital sudden death (OHSD). We sought to examine the association between SIOH and the incidence of OHSD in the diverse neighborhoods of New York City (NYC) during the first wave of COVID-19 epidemic. Methods - NYC ZIP stratified data on OHSD were obtained from the Fire Department of New York during the first wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…In our study, non-Hispanic Black patients were more likely to be enrolled in COVID Watch than usual care, and Hispanic patients were about as likely to be in either group. White, Black, and Hispanic populations also had significantly reduced mortality when enrolled in COVID Watch, and the overall mortality rates were lower relative to reports nationally ( 28 , 39 , 51 , 52 ). These findings suggest no substantial racial or ethnic barriers to program enrollment or its effectiveness and that implementing this type of remote monitoring service has the potential to reduce racial disparities in regions in which Black and Hispanic patients have decreased access to care and higher mortality rates.…”
Section: Discussionmentioning
confidence: 75%
“…In our study, non-Hispanic Black patients were more likely to be enrolled in COVID Watch than usual care, and Hispanic patients were about as likely to be in either group. White, Black, and Hispanic populations also had significantly reduced mortality when enrolled in COVID Watch, and the overall mortality rates were lower relative to reports nationally ( 28 , 39 , 51 , 52 ). These findings suggest no substantial racial or ethnic barriers to program enrollment or its effectiveness and that implementing this type of remote monitoring service has the potential to reduce racial disparities in regions in which Black and Hispanic patients have decreased access to care and higher mortality rates.…”
Section: Discussionmentioning
confidence: 75%
“…Self-identified Black patients and those from poorer neighborhoods who contracted SARS-CoV-2 were more likely to be hospitalized and have worse inpatient outcomes when compared to White patients and those from more affluent areas [ 15 , 16 ]. Regarding cardiovascular disease specifically, Black patients have had higher rates of hospitalization from myocardial infarction and greater event rates of sudden cardiac death during the COVID-19 pandemic when compared to prior studies [ 17 , 18 ]. Interestingly though, our study showed a decrease in admissions for non-Hispanic Black patients and no difference in rates of hospitalization for ADHF for other racial and ethnic minority groups.…”
Section: Discussionmentioning
confidence: 99%
“…This reality for minority patients is especially important to consider in the midst of the COVID-19 pandemic, an illness that has impacted minority communities disproportionately and has also caused a rise in the overall incidence of OHCA. 46 To protect these high-risk communities going forward, greater community outreach is necessary, with instructions in bystander CPR and AED usage that are linguistically and culturally appropriate. EMS resuscitation and hospital postresuscitation protocols must also be reviewed, revised, and standardized to ensure efficiency and accuracy.…”
Section: Discussionmentioning
confidence: 99%